Germination and Seed Vigour in Accelerated Aged Seeds of Rice (Oryza sativa L.) - C.B. SINGH GANGWAR; V.P. KANAUJIA (Seed Research, 2026)
Accelerated ageing test, a test for evaluating the vigour, viability and storability was employed for testing rice cultivars. For this ten cultivars of rice viz. Usar 1, Type 3, Ashwani, Mahsuri, Saket 4, Type 9, Sarju 52, Basmati 370, Prasad and NDR 118 were subjected to accelerated ageing for 0, 3, 5, 7, 9, 12, 15 and 20 days. The changes in germination, seedling length and seed vigour index was studied. These attributes were highly influenced by accelerated ageing and were significantly reduced with advancement of accelerated ageing. Minimum values were recorded after 20 days of accelerated ageing. The data recorded suggested that cultivar Saket 4, NDR 118 and Usar 1 had better germination, seedling length and seed vigour index can withstand well in adverse storage and field conditions during germination.